Restraints of The Labor's Welfare in Lynn Nottage's Play Sweat (2015) - Citra Aidilla; Desvalini Anwar (Universitas Negeri Padang, 2019)
The purpose of this analysis is to expose the issue about restraints of the labor’s welfare which is done by the company in Reading, Pennsylvania and to know the contribution of the plot, setting, and character in revealing the restraints of the labor’s welfare. This analysis is related to the concept alienation by Karl Marx that is supported by the text and context-based interpretation. The result of this analysis shows the company in Reading, Pennsylvania do many things to limiting, controlling, and stopping the labor’s welfare to get much profit.